Maintaining the Partnership Between a Tribal Breast and Cervical Cancer Program and a University-Based Cancer Prevention Center During COVID-19 Lock-Down Restrictions-A Case Study - Teufel-Shone, Nicolette I.; Goldtooth-Begay, Carol; Begay, Andria B.; Lazaro, Ashley; Yellowhair, Janet; Todecheenie, Rolanda; Begay, Delila; Singer, Darlene; Briscoe, Curtis (Frontiers in Public Health, 2022)
To inform women of the Navajo Nation of safety measures implemented to minimize COVID-19 virus exposure during screening and treatment procedures at Navajo Nation based health care facilities, the Navajo Nation Breast and Cervical Cancer Prevention Program (NNBCCPP) and the University-based Partnership for Native American Cancer Prevention Program (NACP) collaborated to develop a podcast to describe the continued availability of services. During the COVID-19 pandemic, women of all ages and ethnicities in the US needing breast and cervical cancer prevention screenings and treatment, have been hesitant to seek services given the advice to avoid crowded spaces and maintain physical distancing. Epidemiological trends indicate that proactive, intensive strategies are needed in Native American communities for early detection and treatment to support early cancer diagnosis and improve cancer survival. The NNBCCPP and Northern Arizona University (NAU) through the National Institute of Health's National Cancer Institute funded NACP had a nascent partnership prior to the onset of COVID-19 pandemic. This partnership relied on face-to-face interaction to allow for informal social interaction, facilitate clear communication and support continued trust building. To adhere to federal, state and tribal recommendations to minimize gatherings and to stay in-place to minimize the spread of the virus, the Navajo Nation and NAU restricted, and in most cases would not approve employee travel for partnership meetings. The plans to develop a podcast necessitated bringing additional members into the collaboration who were unfamiliar to the original partners and due to travel restrictions, required all interactions to be remote. This expanded group met virtually to develop a script, record and edit the podcast. More importantly, group members had to build and maintain trust over months of communicating via a teleconference video platform. This collaborative addressed challenges related to unstable Internet connections and periodic stay-at-home policies; thus, these emerging partners had to modify social and professional communication to respect and accommodate the stress and uncertain circumstances created by the pandemic on the citizens and employees of Navajo Nation. This case study describes strategies used to maintain and respect all members of the partnership.